Bank Sectoral Concentration and Risk: Evidence from a Worldwide Sample of Banks. Issue 6 (9th February 2022) - Beck, Thorsten; De Jonghe, Olivier; Mulier, Klaas
Abstract: We propose a novel, stock‐return based, technique to measure three aspects of banks' sectoral concentration that feature prominently in episodes of bank risk: specialization (capturing high exposures), differentiation (capturing deviation from peer banks), and financial sector exposure (capturing direct connectedness) and show external validity for these measures. We find that both individual and systemic bank risk decrease with specialization. Differentiation is particularly and positively related to individual bank risk, whereas direct connectedness of banks is particularly and positively related to systemic bank risk. These findings inform the theoretical and policy debate on the relationship between sectoral concentration and banks' stability.